The problems of using alcohol biofuel mixtures in the Lithuanian transport system - Lebedevas, Sergejus; Lebedeva, Galina (Transport, 2009)
The article presents the technological aspects of the problems aimed at using alcohol biofuel mixtures in diesel engines kept in operation in Lithuania concerning a gradual replacement of fuel oils with biofuels. It is shown that three‐component fuels such as D‐RME‐E possess the motor characteristics close to mineral diesel fuel. The use of the EC standardized rapeseed oil methyl esters RME as a solvent allows compensating the unfavorable motor characteristics of ethanol E and increasing the number of biocomponents in the fuel at the same time. The key aspects of research on the indicator process and the operating characteristics of diesel engines running on alcohol biofuel mixtures are substantiated.First published online: 27 Oct 2010